Fabrication of Doxorubicin‐Loaded Glycyrrhetinic Acid‐Biotin‐Starch Nanoparticles and Drug Delivery Into HepG2 Cells In Vitro. (9th September 2018) - Chen, Kuanmin; Zhang, Song; Wang, Hui; Wang, Xue; Zhang, Yue; Yu, Lizhen; Ke, Lixia; Gong, Renmin
Abstract : In this article, amphiphilic self‐assembled glycyrrhetinic acid‐biotin‐starch nanoparticles (GaBS NPs) are fabricated by an N, N ′‐dicyclohexylcarbodiimide (DCC)/4‐dimethylaminopyridine (DMAP)‐mediated one‐step esterification reaction, and the physicochemical properties of the prepared self‐assembled NPs are characterized. The self‐assembled GaBS NPs are used as targeted nanocarriers to deliver doxorubicin (DOX) into hepatoma carcinoma cells (HepG2 cells). The drug release profile, cytotoxicity, cellular uptake, and intracellular distribution of the drug‐loaded NPs are evaluated in vitro. Because of endocytosis mediated by a specific receptor, the DOX/GaBS NPs in three forms of administration exhibit the lowest IC50 value to HepG2 cells. The cellular uptake mechanism of pure DOX and the DOX/GaBS NPs is identified by confocal laser scanning microscopy (CLSM), and the cell internalization of the drug‐loaded NPs is confirmed to be faster than that of pure DOX. The GaBS NPs are considered to have potential as a promising chemotherapeutic drug nanocarrier targeting hepatoma carcinoma cells for reducing side effects to normal tissues. Abstract : Amphiphilic self‐assembled glycyrrhetinic acid‐biotin‐starch nanoparticles (GaBS NPs) are fabricated. The cellular uptake mechanism of pure DOX and the DOX/GaBS NPs is identified by confocal laser scanning microscopy (CLSM), and the cell internalization of the drug‐loaded NPs is confirmed to be faster than that of pure DOX.